2017
DOI: 10.1016/j.cmet.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Hepatic mTORC1 Signaling via Dose-Dependent Mechanisms Involving AMPK and the TSC Complex

Abstract: Metformin is the most widely prescribed drug for the treatment of type-2 diabetes. However, knowledge of the full effects of metformin on biochemical pathways and processes in its primary target tissue, the liver, is limited. One established effect of metformin is to decrease cellular energy levels. The AMP-activated protein kinase (AMPK) and mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) are key regulators of metabolism that are respectively activated and inhibited in acute response to cellular ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
250
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(261 citation statements)
references
References 48 publications
11
250
0
Order By: Relevance
“…In addition, both galegine (a related guanide compound) and metformin suppressed hepatic gluconeogenesis within 20 min of intravenous infusion in rats, a time frame that is inconsistent with that of transcriptional mechanisms 83 . In hepatocytes, the activation of AMPK in response to guanide and biguanide compounds is well established 78,80,82,8486 and occurs rapidly following the intravenous administration of galegine 83 . However, interestingly, pharmacological activation of AMPK with A-769662 (which activates AMPK to a similar extent to galegine) did not suppress HGP in awake hepatic glycogen-depleted rats 83 .…”
Section: Control Of Hepatic Gluconeogenesismentioning
confidence: 99%
“…In addition, both galegine (a related guanide compound) and metformin suppressed hepatic gluconeogenesis within 20 min of intravenous infusion in rats, a time frame that is inconsistent with that of transcriptional mechanisms 83 . In hepatocytes, the activation of AMPK in response to guanide and biguanide compounds is well established 78,80,82,8486 and occurs rapidly following the intravenous administration of galegine 83 . However, interestingly, pharmacological activation of AMPK with A-769662 (which activates AMPK to a similar extent to galegine) did not suppress HGP in awake hepatic glycogen-depleted rats 83 .…”
Section: Control Of Hepatic Gluconeogenesismentioning
confidence: 99%
“…This mouse model revealed that these phosphorylation events mediate the insulin-sensitizing effect of metformin, thus establishing AMPK as a relevant target in the action of metformin. Despite controversy 224 , AMPK is widely viewed as an essential component of the action of metformin at physiological concentrations 219,225 . Given the role of the AMPK–ACC pathway in regulating fatty acid synthesis, AMPK activation is also an attractive treatment option for conditions associated with increased fatty acid production, such as nonalcoholic fatty liver disease (NAFLD) 85 .…”
mentioning
confidence: 99%
“…We acknowledge that the role of mTOR signaling in myocardial IRI is complex and depends on its temporal activation pattern, the cell type, the extent of mTOR activity, and the involvement of mTORC1 vs mTORC2. 14,41,60 The ability of TSC1 deficiency to abolish aPC-mediated mTORC1 inhibition indicates that aPC regulates the mTORC1 complex. 60,61 However, considering the multifaceted interactions of TSC1/TSC2, mTORC1, and mTORC2, the precise mechanism needs to be evaluated in future studies.…”
Section: 5152mentioning
confidence: 99%
“…TSC1 is a pivotal inhibitor of mTORC1, and its deficiency causes constitutive mTORC1 activation. 41 BMDMs were isolated from mice with inducible TSC1 deficiency, and TSC1 expression was inhibited by transient expression with Cre recombinase ex vivo 41 ( Figure 4F; control cells transiently expressed GFP). In TSC1-deficient BMDMs, aPC failed to inhibit expression of Raptor and HK1 and phosphorylation of p70S6K ( Figure 4G-H), and importantly, aPC-mediated Nlrp3 inflammasome restriction was abolished ( Figure 4I-J).…”
Section: Apc Restricts Inflammasome By Suppressing Mtorc1 and Hk1mentioning
confidence: 99%